Equivalent Moduli of Carcass Layer in Flexible Pipes - Wang, Wei; Chen, Geng; Liu, Yang (Asian Journal of Chemistry, 2014)
Flexible pipes, as a typical composite structure, are generally applied to the ocean oil engineering. The Carcass layer of flexible pipes, with its particular structural formation, demonstrates orthotropic properties and the moduli of the Carcass layer are not the material moduli. Just the moduli of the Carcass layer are calculated, the whole structure will be analyzed. In the present paper, the equivalent modulus equations of the Carcass layer are deduced with the use of the ideology that under the same loading, the similar material and the original material have the same displacement. This analytical method of equivalent moduli shows good capacity in the prediction of the behaviour of the flexible pipes, which provides practical and technical support for the application of unbonded flexible pipes.